Pengaruh Latihan Small Sided Games terhadap Peningkatan Kemampuan Passing pada Tim Futsal Putri SMKN 4 Kota Jambi - Al-Rahmatsyah, M. Sultan; Munar, Hendri; Hasibuan, Usni Zamzami (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to evaluate the effectiveness of small sided games training methodology in developing ball passing skills among female futsal team members of SMKN 4 Jambi City. In the context of futsal, passing competency serves as a fundamental technical element that directly influences team gameplay quality. The study utilized a quantitative methodology with a pre-experimental framework, implementing a single-group assessment model that measured outcomes both before and after the intervention. The research sample encompassed the entire population of the female futsal team at SMKN 4 Jambi City, totaling 15 athletes. The evaluation instrument consisted of a low ball passing test, while the treatment involved a small sided games program implemented over 16 training sessions. Analysis results revealed substantial improvement in passing skills, marked by an increase in average scores from 3.93 during pretest to 6.87 at posttest. Hypothesis testing through one-sample t-test demonstrated a significance value (2-tailed) of 0.001 < 0.05 with a mean difference of 3.267. These findings indicate that the implementation of small sided games training effectively enhanced passing quality among female futsal players at SMKN 4 Jambi City.